2008
DOI: 10.1007/s10637-008-9178-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of chemoradiation therapy with weekly oxaliplatin and protracted infusion of 5-fluorouracil for esophageal cancer

Abstract: Although weekly oxaliplatin in combination with infusional 5 fluorouracil produces durable remissions in esophageal cancer, the regimen used in this trial was not acceptable for routine use. Future protocols should incorporate lower chemotherapy doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…2,3 Considerable efforts have been made to identify novel and reliable biomarkers for early diagnosis, more effective combination chemotherapy strategies, and possible mechanisms of chemoresistance. [4][5][6] A recent study indicates that autophagy is a survival mechanism that promotes chemoresistance and that regulators selectively inhibiting autophagy have the potential to improve chemotherapeutic regimes in esophageal cancer cells. 7 Autophagy is an evolutionarily conserved survival response to growth-limiting conditions, in which cytosolic proteins or damaged organelles are sequestered, degraded, and released for recycling.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Considerable efforts have been made to identify novel and reliable biomarkers for early diagnosis, more effective combination chemotherapy strategies, and possible mechanisms of chemoresistance. [4][5][6] A recent study indicates that autophagy is a survival mechanism that promotes chemoresistance and that regulators selectively inhibiting autophagy have the potential to improve chemotherapeutic regimes in esophageal cancer cells. 7 Autophagy is an evolutionarily conserved survival response to growth-limiting conditions, in which cytosolic proteins or damaged organelles are sequestered, degraded, and released for recycling.…”
Section: Introductionmentioning
confidence: 99%
“…However, single-agent chemotherapy is not effective for esophageal cancer because of natural resistance and the development of resistance (4). In esophageal cancer, many studies have demonstrated that combination therapy is more effective than single-drug therapy (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The cord dose described in other studies is: 42 Gy [13]; 41 Gy [16]. The reduction in cord dose could be of significance, as new evidence suggests that cord dose should not exceed 40 Gy in cases of combined modality with oxaliplatin [38,39].…”
Section: Volumetric Modulated Arc Therapy For Oesophageal Malignanciesmentioning
confidence: 91%